Analysing price behaviour and forecasting of orange prices in South Africa from 2001 to 2021 - Mashita, M. M. (My University, 2024)
The citrus sector in South Africa exports more than 60% of the citrus produced in the Southern Hemisphere, making it the leading citrus exporter in the region. After Spain, South Africa is the country that exports the most citrus. However, the increased trend in orange pricing over the past 20 years is a sign of a strong sector with room to expand as demand outstrips supply. The forecasting of agricultural commodity futures prices has a significant impact on the stability of the market economy and is essential to economic progress. The study aimed to analyse price behaviour and forecasting of orange prices from 2001 to 2021. The objectives were to determine trends in the price behaviour of oranges in South Africa from 2001 to 2021 and forecast orange prices from 2022 to 2026. The study used secondary time series data from 2001 until 2021 of price measured in rands and yield in tonnes. The first objective was addressed by Ordinary Least Squares (OLS) and descriptive statistics and results revealed that there are upward and downward trends in price of oranges. Objective two was to forecast future orange prices. Supplemental the study went on to determine the values of p, d, and q in addition using Dickey-Fuller Test to assess stationarity at first. The average price was found to be 275.81 in million rands, while the average yield was found to be 14839830 in tonnes. Moreover, ARIMA 512 was estimated to be fit for forecasting because it had the highest adjusted R squared value of 0.272978 than other identified models. Therefore, the study recommends that farmers work with agricultural advisors to make fruitful decisions and farmers also need to understand and learn models of forecasting to be aware of future prices of goods and services. The state should also make sure there is flow of information in the agricultural sector.
Thesis (M.Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2024
Keywords: Orange; Price trends; Yield; ARIMA; Forecasting; Orange -- Yields; Consumer price indexes; Citrus fruit industry